ORGANIC PRODUCTION IN GREECE – CHALLENGES AND LESSONS LEARNED - Sdrolias Labros; Grigoriou Ioanna; Anyfantis Ioannis; Nousia Maria; Koukoumpliakos Ioannis; Kiriakou D. (European Scientific Journal, ESJ, 2014)
Organic production has gradually entered the lives of Greek farmers and citizens during the last few years and quickly proved to be a very realistic and lucrative alternative, having tremendous appeal. Even though initial reticence was quickly succeeded by enthusiasm, recently there has been a noticeable lack of interest among farmers regarding biological agriculture. Organic production adopts a production system reflecting health of soil, ecosystems and people proposing an overall attitude of farm management and food production that combines best environmental practices, a high level of biodiversity, conservation of natural resources, application of high standards on animal welfare and production in line with the preference of certain consumers for products produced using natural substances and processes. In this paper we will try to present the concerns grown regarding the utilization of organic production in Greece. This study is based on research of written documents, the use of historical method and other research methods. The findings of the study are particularly important and any utilization will contribute substantially to the study of further development of biological agriculture in our country.